Development of readout electronics for high resolution neutron scintillator detector - ZHOU Shihui; HUANG He; WAN Zhiyong; CHEN Shaojia; ZHU Zhifu; TANG Bin; HUANG Chang; WANG Xiuku; ZENG Lixin; YU Li; YANG Hao; LIU Huiyin; et al. (He jishu, 2023)
BackgroundThe Energy Resolved Neutron Imaging Spectrometer (ERNI) of China Spallation Neutron Source (CSNS) is in process of building, whose diffraction detector with ninety degree partition adopts 6LiF/ZnS neutron scintillator detector with a 90° partition as its detection equipment.PurposeThis study aims to develop the readout electronics for high position resolution neutron scintillator detector of ERNI.MethodsFirstly, a capacitive network combined with center-of-gravity of the induced charge distribution was adopted for the design of readout electronics. Then, a prototype of the readout electronics system consisted of three parts: capacitive network circuit, preamplifier board and digital readout board, was developed. After functional verification, the relevant performance parameters of the developed prototype were experimentally tested in the laboratory and in the No.20 beam line of CSNS.ResultsThe experimental results show that the integration nonlinearity of electronics is better than 0.95%, the time resolution is about 12 ns, the position resolution is 1mm, and the detection efficiency is 65%@1.6 Å.ConclusionsThe prototype meets the design specifications of the project. The successful development of the prototype provides a reliable technical support for the smooth development of the spectrometer experiment in ERNI of CSNS in the future.